Comparative hygienic risk assessment of groundwater contamination by herbicides of different chemical classes and hazard prediction for human after consumption of contaminated water = Порівняльна гігієнічна оцінка ризику забруднення підземних вод гербіцидами різних класів та прогноз небезпеки для людини при споживанні забрудненої води. - A. M. Antonenko; O. P. Vavrinevych; S. T. Omelchuk; M. M. Korshun (Journal of Education, Health and Sport, 2016)
Antonenko A. M., Vavrinevych O. P., Omelchuk S. T., Korshun M. M. Comparative hygienic risk assessment of groundwater contamination by herbicides of different chemical classes and hazard prediction for human after consumption of contaminated water  = Порівняльна гігієнічна оцінка ризику забруднення підземних вод гербіцидами різних класів та прогноз небезпеки для людини при споживанні забрудненої води. Journal of Education, Health and Sport. 2016;6(9):873-882. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.161844